English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-03 07:34:05 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

We have f(x) = (x)^(7x) = e^(7x*ln(x)). So, f'(x) = e^(7x*ln(x)) * d/dx(7x*ln(x) = . (x)^(7x) *7 *(x *1/x + ln(x) = 7* (1+lnx) * (x)^(7x)

2006-11-03 07:58:59 · answer #1 · answered by Steiner 7 · 0 0

The derivative is 7x * x^6x * 7 = 49x^(6x+1)

~ ♥ ~

2006-11-03 07:50:07 · answer #2 · answered by I ♥ AUG 6 · 0 1

fedest.com, questions and answers